Mental health mobile apps review: Islamic design and content features in digital therapeutics - Mahmud, Murni; Samsuri, Suhaila; Zannat, Nahreen; Nowshin, Nadia (Design for Scientific Renaissance, 2022)
In pandemic Covid-19, mental health and well-being become one of the major concerns for human beings for appeasement in every sphere of life. During a lockdown, the pressure and stress have led to the financial burden, increasing depression, suicides and anxiety. Correspondingly, use of devices, intenet and mobile applications are increasing and disruptive. This include the use of mobile application for mental health solution which could be catagorised as Digital Therapeutics (DTx). Some DTx have been designed and developed especially for the people who have been directly or indirectly encountered mental health issues. Literatures indicate the understanding of the Islamic design and content for features for DTx are scarce; therefore, this paper aims to report a review of mobile applications to identify design and Content features for establishing understanding DTx from Islamic point of view. Selected mental health mobile applications have been selected, reviewed and analysed. The findings shows Islamic design and Content features can be identified and recognised. It is speculated the Islamic design and content features are potential to alleviate some suffering of mental health and to sustain wellbeing in digital living.